Pemberdayaan Masyarakat Nongsa dengan Pembelajaran Penentuan Daerah Penangkapan Ikan Berbasis Teknologi di Bidang Kelautan - Muhammad Zainuddin Lubis; Wenang Anurogo; Daniel Sutopo Pamungkas (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2018)
The limitation of technology in the marine sector is a big problem faced by every coastal region in Indonesia. By looking at the income levels decreasion in Batam City area and the whole Batam Island, technology is the answer to overcome this problem. This community service activity aims to improve the understanding and skill of coastal community of Bale-Bale, Nongsa, Batam on the mapping and fishing area determination (DPI), intellectual property rights (Fishing Location) , and development of instructional material (textbook) at Batam State Polytechnic Campus. The fishermen at Bale-Bale Beach, Nongsa, Batam have been able to use GPS Map 585, and  depth detection instrument Side Scan Sonar for detecting and saving location which had lots of fish. Based on the results of community service activities, it can be concluded that community participation in Bale-Bale area with more focus is adolescents who have young and skilled soul, is a key factor that determines the success of marine technology utilization process to predict fish stock and helping to improve efficiency levels in the process of going out to sea.